2022
DOI: 10.53730/ijhs.v6ns3.8743
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes resulting from the effect of nano-graphene oxide on the liver in laboratory rats

Abstract: The current study included the use of (48) white male laboratory rats, where the rats were divided into six groups, with 8 rats in each group. The second group with a concentration of 30 mg/kg, the third group with a concentration of 40 mg/kg, the fourth group with a concentration of 50 mg/kg, and the fifth group with a concentration of 60 mg/kg of nano graphene oxide. The sixth group is the control group. The results of the statistical analysis of the study showed a significant decrease in the average body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…[ 86 ] Abd‐Alsahib and Faris in (2022) stated that GO NPs with a concentration of 60 mg/kg/bw caused damages such as dilation of liver sinuses, proliferation of the nucleus of liver cells, thickening of the nucleus in some liver cells, penetration Inflammatory cells, bleeding and dissolution of hepatocytes in mice liver tissue. [ 10 ] Rhazouani et al. (2023) stated that GO NPs cause inflammation in liver cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 86 ] Abd‐Alsahib and Faris in (2022) stated that GO NPs with a concentration of 60 mg/kg/bw caused damages such as dilation of liver sinuses, proliferation of the nucleus of liver cells, thickening of the nucleus in some liver cells, penetration Inflammatory cells, bleeding and dissolution of hepatocytes in mice liver tissue. [ 10 ] Rhazouani et al. (2023) stated that GO NPs cause inflammation in liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 94,95 ] The toxicity of GO NPs has been fully confirmed in various cases, including oxidative stress and lipid peroxidation. [ 10–87 ] As a proposed mechanism to justify these observations, it can be suggested that the EAFE, due to its antioxidant properties, can neutralize free radicals caused by GO NPs and it has the ability to maintain oxidative homeostasis and combat oxidative stress in kidney, lung and testis tissues of mice. [ 96 ] Patlolla et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations